Kinematics and workspace analysis of an exoskeleton for thumb and index finger rehabilitation - Ruoyin Zheng; Jiting Li (2010 IEEE International Conference on Robotics and Biomimetics, 2010)
For the human hand rehabilitation, the palmar opposition is an important function to evaluate the recovery of hand motor capabilities. This paper proposes an exoskeleton-type hand rehabilitation assistive device which is able to be applied to index finger as well as thumb. The kinematics and workspace of index fingertip and thumb-tip are analyzed. The `opposition space' is defined as the intersection of the workspace of thumb-tip and the index fingertip. A metric, what we call `opposition degree', which is defined as the ratio of volume of opposition space to that of the index fingertip workspace, is proposed to present the available degree of opposition. As an example, the opposition degree of a human hand model is determined. This metric can also used to rate the ergonomic performance of the hand rehabilitation assistive device. This method can be applied to other fingers as well. The opposition simulation experiment is conducted to verify the kinematics of the proposed exoskeleton.